Thermoelectric efficiency of single-molecule junctions with long molecular linkers. (2nd July 2018) - Zimbovskaya, Natalya A
Abstract: We report results of theoretical studies of thermoelectric efficiency of single-molecule junctions with long molecular linkers. The linker is simulated by a chain of identical sites described using a tight-binding model. It is shown that thermoelectric figure of merit ZT strongly depends on the bridge length, being controlled by the lineshape of electron transmission function within the tunnel energy range corresponding to HOMO/LUMO transport channel. Using the adopted model we demonstrate that ZT may significantly increase as the linker lengthens, and that gateway states on the bridge (if any) may noticeably affect the length-dependent ZT. Temperature dependences of ZT for various bridge lengths are analyzed. It is shown that broad minima emerge in ZT versus temperature curves whose positions are controlled by the bridge lengths.